2009
DOI: 10.4081/ijas.2009.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rearing system and season on the performance and egg characteristics of Ancona laying hens

Abstract: Productive performance and egg characteristics of Ancona laying hens reared under three different rearing systems (conventional, organic and organic-plus) were compared during an experimental period of one year. Three-hundred-sixty Ancona female chicks at 28 days of age were divided in three groups and assigned to different rearing systems. The organic group had 4m 2 pasture/hen according to the requirements imposed by the EC Regulation 1804/99, whereas the organic-plus group had a larger grass paddock (10m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
71
3
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 34 publications
14
71
3
6
Order By: Relevance
“…It was found that egg cholesterol decreased as alfalfa meal increased in a laying hen diet [62]. Studies demonstrated that hens with access to high-quality pasture had eggs with at least twice as much vitamins A and E and omega-3s, compared to hens having no access to different pastures [68][69][70][71]. Furthermore, it is well established that a large range of forages, such as alfalfa, perennial ryegrass, red clover, and grass meals, although containing significant fiber levels, are valuable sources of xanthophylls and can be successfully used in diets as natural pigmenting agents [72].…”
Section: Influence Of Feeding Forage On Poultry Egg and Meat Qualitymentioning
confidence: 99%
“…It was found that egg cholesterol decreased as alfalfa meal increased in a laying hen diet [62]. Studies demonstrated that hens with access to high-quality pasture had eggs with at least twice as much vitamins A and E and omega-3s, compared to hens having no access to different pastures [68][69][70][71]. Furthermore, it is well established that a large range of forages, such as alfalfa, perennial ryegrass, red clover, and grass meals, although containing significant fiber levels, are valuable sources of xanthophylls and can be successfully used in diets as natural pigmenting agents [72].…”
Section: Influence Of Feeding Forage On Poultry Egg and Meat Qualitymentioning
confidence: 99%
“…Slow-growing birds are more adapted to natural systems, and the quality of their meat is more appropriate for a specialty or gourmet market [6,7] . Thus, some researchers [3,8] stated that slow-growing chickens possess a good aptitude for pasture, which enhances the dietary intake of bioactive substances (i.e vitamins, antioxidants, and fatty acids) contained in the forage. In addition, the free-range chicken can consume young vegetative plant material and live protein sources, such as insects, worms, and grubs, which could reduce the feed cost that accounts for approximately 70% of the total variable costs [9,10] stated that compared with conventional free-range and organic systems, the pastured poultry is likely to induce considerably greater levels of pasture consumption, and thus it is an ideal system to evaluate the nutritional impact of pasture intake in broiler performance and carcass quality.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, linolenic acid is present in structural lipids in the esterified form, including galactolipids from chloroplasts (Gurr, 1984). Total tocopherol content was higher in pasture than in feed, confirming grass as a relevant source of vitamin E (Mugnai et al, 2009). …”
Section: Resultsmentioning
confidence: 94%
“…Grass pasture has to be considered an important source of energy, protein and vitamins able to reduce the consumption of concentrate in free range rabbits. Grass and standard feed had similar content of polyunsaturated fatty acids, but great differences were observed in linoleic and linolenic acid amounts (Mugnai et al, 2009). In particular, linolenic acid is present in structural lipids in the esterified form, including galactolipids from chloroplasts (Gurr, 1984).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation